Recent Advances in Chinese Archeomagnetism - Cai, Shuhui; Tauxe, Lisa; Paterson, Greig A.; Deng, Chenglong; Pan, Yongxin; Qin, Huafeng; Zhu, Rixiang (Frontiers in Earth Science, 2017)
The geomagnetic field is one of Earth’s fundamental properties with a history of ~3.5 Gyr. The field, generated in Earth’s core is a window to the deep interior of Earth and may have played a key role in evolution of life on our planet. Materials on Earth’s surface that contain magnetic minerals can record information about the geomagnetic field in which they formed. Fired archeological materials (e.g., pottery, brick, and burnt clay) are favorable recorders of the field, and have been widely employed to recover geomagnetic variations over periods of hundreds to thousands of years. The longevity of Chinese civilization and the abundant nature of archeological artifacts make Chinese archeomagnetism a promising source of data. The main work of Chinese archeomagnetism was carried out in the 1980s and 90s, followed by a break of more than a decade; in the 2010s activity resumed. In this paper, we review the development of Chinese archeomagnetism, including a summary of previous work, recent progress, remaining issues and future studies with the aim of promoting an understanding of archeomagnetic work in China and to guide the way for future studies. Here, we compile published data, including some data discovered in old publications that have not yet been included in paleomagnetic databases. We also establish the first, albeit preliminary, archeomagnetic reference curves (with 42 declination / inclination pairs and 76 / 192 archeointensities) for the geomagnetic field in China (ArchInt_China.1a / ArchInt_China.1b, ArchDec_China.1, ArchInc_China.1), which can be used for global comparison of the field and regional archeomagnetic dating.